Physician associates working in secondary care teams in England: Interprofessional implications from a national survey. Issue 6 (2nd November 2017) - Wheeler, Carly; Halter, Mary; Drennan, Vari M.; de Lusignan, Simon; Grant, Robert; Gabe, Jonathan; Gage, Heather; Begg, Philip; Ennis, James; Parle, Jim
ABSTRACT: Physician associates (PAs) are a new type of healthcare professional to the United Kingdom; however, they are well established in the United States (where they are known as physician assistants). PAs are viewed as one potential solution to the current medical workforce doctor shortage. This study investigated the deployment of PAs within secondary care teams in England, through the use of a cross-sectional electronic, self-report survey. The findings from 14 questions are presented. Sixty-three PAs working in a range of specialties responded. A variety of work settings were reported, most frequently inpatient wards, with work generally taking place during weekdays. Both direct and non-direct patient care activities were reported, with the type of work undertaken varying at times, depending on the presence or absence of other healthcare professionals. PAs reported working within a variety of secondary care team staffing permutations, with the majority of these being interprofessional. Line management was largely provided by consultants; however day-to-day supervision varied, often relating to different work settings. A wide variation in ongoing supervision was also reported. Further research is required to understand the nature of PAs' contribution to collaborative care within secondary care teams in England.